Numerical study on the stiffness and ultimate strength of cold-formed steel C-shaped connectors under pull-out failure - Obeydi, Marzieh; Baltork, Iman Mohammadpoor; Zeynalian, Mehran (Australian journal of structural engineering, 2023)
In this paper, cold-formed steel C-shaped connectors, as one of the most commonly used components in steel wall/framing systems, were investigated under the pull-out failure modes using a detailed numerical study. Finite element models were validated using the data obtained from an experimental program; and the results were compared with the current design equations. Finally, a new pull-out strength equation was proposed based on the critical parameters affecting the behaviour of C-shaped connectors. In addition, initial bending stiffness of C-shaped connectors was studied using a simplified analytical approach; and the results obtained from the proposed new stiffness equation were compared with the initial slope of experimental and numerical force-displacement curves. These comparisons confirm the accuracy of the new strength and stiffness equations in order to apply to the analytical methods such as component-based method in future works.